Comparative Ecophysiological Study of Salt Stress for Wild and Cultivated Soybean Species from the Yellow River Delta, China - Gang Wu; Zhengda Zhou; Peng Chen; Xiaoli Tang; Hongbo Shao; Hongyan Wang (The Scientific World Journal)
Osmotic and ionic stresses were the primary and instant damage produced by salt stress. They can also bring about other secondary stresses. Soybean is an important economic crop and the wild soybean aroused increasing attention for its excellent performance in salt resistance. For this reason, we compared the different performances of Glycine max L. (ZH13) and Glycine soja L. (BB52) in both young and mature seedlings, hoping to clarify the specific reasons. Our research revealed that, compared to the cultivated soybean, the wild soybean was able to maintain higher water potential and relative water content (RWC), accumulate more amount of proline and glycine betaine, reduce the contents of Na+ and Cl− by faster efflux, and cut down the efflux of the K+ as well as keep higher K+/Na+ ratio. And what is more is that, almost all the excel behaviors became particularly obvious under higher NaCl concentration (300 mM). Therefore, according to all the detections and comparisons, we concluded that the wild soybean had different tolerance mechanisms and better salt resistance. It should be used as eminent germplasm resource to enhance the resistant ability of cultivated soybean or even other crops.